Clonal and serotype dynamics of serogroup 6 isolates causing invasive pneumococcal disease in Portugal: 1999-2012. - Jorge Diamantino-Miranda; Sandra Isabel Aguiar; João André Carriço; José Melo-Cristino; Mário Ramirez (PLoS ONE)
Although serogroup 6 was among the first to be recognized among Streptococcus pneumoniae, several new serotypes were identified since the introduction of pneumococcal conjugate vaccines (PCVs). A decrease of the 6B-2 variant among invasive pneumococcal disease (IPD), but not 6B-1, was noted post conjugate vaccine introduction, underpinned by a decrease of CC273 isolates. Serotype 6C was associated with adult IPD and increased in this age group representing two lineages (CC315 and CC395), while the same lineages expressed other serogroup 6 serotypes in children. Taken together, these findings suggest a potential cross-protection of PCVs against serotype 6C IPD among vaccinated children but not among adults. Serotype 6A became the most important serogroup 6 serotype in children but it decreased in adult IPD. No other serogroup 6 serotypes were detected, so available phenotypic or simple genotypic assays remain adequate for distinguishing serotypes within serogroup 6 isolates.